2022
DOI: 10.5755/j01.ee.33.1.28716
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Entrepreneurial Intentions of Youth: The Role of Access to Finance

Abstract: This study aims to highlight the role of access to finance as one of the determinants on the decision to enter into entrepreneurship of students regarded as potential entrepreneurs. For achieving our main objective, we created a questionnaire. As a method of analysis, we run the least square logistic regression, with entrepreneurial intentions as a dependent variable and knowledge, education and availability of financial resources as predictors. We also included gender, university and locality as control varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…While previous studies have primarily focused on the positive side of family background, such as role modeling by entrepreneurial family members (Lee et al, 2021;Zhang and Huang, 2021), this study focuses on the negative aspects. Entrepreneurship education will improve students' understanding of entrepreneurship, but it also means that students will realize the high risks and investment of entrepreneurship, which requires a good family economic foundation (Rusu et al, 2022). This study argues that poor families may induce timidity, even for students with increased entrepreneurial knowledge and improved entrepreneurial ability.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…While previous studies have primarily focused on the positive side of family background, such as role modeling by entrepreneurial family members (Lee et al, 2021;Zhang and Huang, 2021), this study focuses on the negative aspects. Entrepreneurship education will improve students' understanding of entrepreneurship, but it also means that students will realize the high risks and investment of entrepreneurship, which requires a good family economic foundation (Rusu et al, 2022). This study argues that poor families may induce timidity, even for students with increased entrepreneurial knowledge and improved entrepreneurial ability.…”
Section: Discussionmentioning
confidence: 90%
“…High uncertainty is one of the characteristics of entrepreneurship (McMullen and Shepherd, 2006), and it also necessitates the acquisition of initial funds by entrepreneurs (Calic and Mosakowski, 2016). Research has shown that the family is an important source of start-up capital (Elston et al, 2016), especially for young college students (Rusu et al, 2022). The implementation of entrepreneurship education will assist students in acquiring corresponding entrepreneurial knowledge, allowing them to gain a preliminary understanding of the capital needs and risks involved in the entrepreneurship process.…”
Section: Family Economic Statusmentioning
confidence: 99%
See 2 more Smart Citations
“…The assessment of young adults ' entrepreneurial intentions and behaviour determinants has been thoroughly analysed in various scientific research papers. A continuous reviving of the topic is absolutely necessary (Rusu et al. , 2022; Owczarek and Wiktorowicz, 2018).…”
Section: General Backgroundmentioning
confidence: 99%